1997
DOI: 10.1029/97gl01547
|View full text |Cite
|
Sign up to set email alerts
|

Unique products of the reaction of isoprene with atomic chlorine: Potential markers of chlorine atom chemistry

Abstract: Abstract. The contribution of atomic chlorine to the chemistry of marine regions as well as the Arctic at ground level at polar sunrise is the subject of a number of recent studies. However, identifying the specific chlorine atom precursors has proven difficult. One potential approach is the measurement of definitive products of chlorine atom reactions, for example with biogenic hydrocarbons. We report here product studies of the chlorine atom reaction with isoprene using ppm concentrations at one atmosphere a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 27 publications
6
60
0
Order By: Relevance
“…S12). The formation of C 5 H 8 O from chlorine-isoprene oxidation has been proposed in the literature (Nordmeyer et al, 1997). Previous studies that observed C 5 H 8 O during OH-initiated oxidation of isoprene identified it as 2-methylbut-3-enal, but its formation mechanism remains unclear (Brégonzio-Rozier et al, 2015;Healy et al, 2008) and is beyond the scope of this work.…”
Section: Soa Yieldmentioning
confidence: 79%
See 3 more Smart Citations
“…S12). The formation of C 5 H 8 O from chlorine-isoprene oxidation has been proposed in the literature (Nordmeyer et al, 1997). Previous studies that observed C 5 H 8 O during OH-initiated oxidation of isoprene identified it as 2-methylbut-3-enal, but its formation mechanism remains unclear (Brégonzio-Rozier et al, 2015;Healy et al, 2008) and is beyond the scope of this work.…”
Section: Soa Yieldmentioning
confidence: 79%
“…Previous studies that observed C 5 H 8 O during OH-initiated oxidation of isoprene identified it as 2-methylbut-3-enal, but its formation mechanism remains unclear (Brégonzio-Rozier et al, 2015;Healy et al, 2008) and is beyond the scope of this work. It should be noted that CMBO has long been identified as a unique gas-phase marker for isoprene-chlorine oxidation (Chang and Allen, 2006;Nordmeyer et al, 1997;Riemer et al, 2008;Tanaka et al, 2003). Degradation of CMBO by OH is implemented in some air quality models, though only with inferred reaction rates ).…”
Section: Soa Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Isoprene and the monoterpenes are also quite reactive and have atmospheric lifetimes of considerably less than a day. Like most VOC, the daytime oxidation of biogenic VOC is initiated primarily by reaction with OH, however reaction with O 3 , NO 3 , and Cl can also be important under some circumstances for some compounds (Atkinson, 1994(Atkinson, , 1997Atkinson and Arey, 1998;Nordmeyer et al, 1997;Paulson et al, 1992a, b).…”
Section: Speciationmentioning
confidence: 99%